Pre-Replicative Repair of Oxidized Bases Maintains Fidelity in Mammalian Genomes: The Cowcatcher Role of NEIL1 DNA Glycosylase - Rangaswamy, Suganya (Genes (Basel), 2017)
Genomic fidelity in the humans is continuously challenged by genotoxic reactive oxygen species (ROS) generated both endogenously during metabolic processes, and by exogenous agents. Mispairing of most ROS-induced oxidized base lesions during DNA replication induces mutations. Although bulky base adducts induced by ultraviolet light and other environmental mutagens block replicative DNA polymerases, most oxidized base lesions do not block DNA synthesis. In 8-oxo-G:A mispairs generated by the incorporation of A opposite unrepaired 8-oxo-G, A is removed by MutYH (MYH) for post-replicative repair, and other oxidized base lesions must be repaired prior to replication in order to prevent mutation fixation. Our earlier studies documented S phase-specific overexpression of endonuclease VIII-like 1 (NEIL1) DNA glycosylase (DG), one of five oxidized base excision repair (BER)-initiating enzymes in mammalian cells, and its high affinity for replication fork-mimicking single-stranded (ss)DNA substrates. We recently provided experimental evidence for the role of NEIL1 in replicating-strand repair, and proposed the “cowcatcher” model of pre-replicative BER, where NEIL1’s nonproductive binding to the lesion base in ssDNA template blocks DNA chain elongation, causing fork regression. Repair of the lesion in the then re-annealed duplex is carried out by NEIL1 in association with the DNA replication proteins. In this commentary, we highlight the critical role of pre-replicative BER in preventing mutagenesis, and discuss the distinction between pre-replicative vs. post-replicative BER.